Quadratic Straightedge and Compass Solver

Geometry Level 3

Given integer values of a a , b b , and c c , use a straightedge and compass to construct rectangle P Q T U PQTU such that P Q = 1 PQ = 1 and P U = b a PU = \frac{b}{a} , and then construct rectangle P R S U PRSU such that P R = c a PR = \frac{c}{a} . Then construct the diagonals of rectangle Q R S T QRST and call their intersection X X , and finally construct a circle with center X X and radius X Q XQ . Let the intersection points of the circle and P U PU be W W and V V .

Then the lengths of P W PW and P V PV are solutions to which of the following quadratic equations?

(inspired by the book Number: The Language of Science by Tobias Dantzig)

a x 2 + b x + c = 0 ax^2 + bx + c = 0 a x 2 b x c = 0 ax^2 - bx - c = 0 a x 2 b x + c = 0 ax^2 - bx + c = 0 a x 2 + b x c = 0 ax^2 + bx - c = 0

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

David Vreken
Jun 6, 2018

Let P P be the origin. Then Q Q has coordinates ( 0 , 1 ) (0, 1) and X X has coordinates ( b 2 a , c + a 2 a ) (\frac{b}{2a}, \frac{c + a}{2a}) .

Using the distance formula on X Q XQ , X Q 2 = ( c a 2 a ) 2 + ( b 2 a ) 2 XQ^2 = (\frac{c - a}{2a})^2 + (\frac{b}{2a})^2 .

Then the circle has an equation of ( x b 2 a ) 2 + ( y c + a 2 a ) 2 = X Q 2 (x - \frac{b}{2a})^2 + (y - \frac{c + a}{2a})^2 = XQ^2 , or ( x b 2 a ) 2 + ( y c + a 2 a ) 2 = ( c a 2 a ) 2 + ( b 2 a ) 2 (x - \frac{b}{2a})^2 + (y - \frac{c + a}{2a})^2 = (\frac{c - a}{2a})^2 + (\frac{b}{2a})^2 .

Since P P is the origin, P U PU is the x x -axis, and W W and V V are the x x -intercepts of the circle when y = 0 y = 0 , so ( x b 2 a ) 2 + ( 0 c + a 2 a ) 2 = ( c a 2 a ) 2 + ( b 2 a ) 2 (x - \frac{b}{2a})^2 + (0 - \frac{c + a}{2a})^2 = (\frac{c - a}{2a})^2 + (\frac{b}{2a})^2 , which simplifies to x = b ± b 2 4 a c 2 a x = \frac{b \pm \sqrt{b^2 - 4ac}}{2a} . Substituting b -b' for b b gives x = b ± b 2 4 a c 2 a x = \frac{-b' \pm \sqrt{b'^2 - 4ac}}{2a} , which is the quadratic equation that would solve a x 2 + b x + c = 0 ax^2 + b'x + c = 0 , and since b = b b' = -b , this straightedge and compass method solves a x 2 b x + c = 0 ax^2 - bx + c = 0 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...